Three Collections of Gǝʿǝz Manuscripts Recently Surveyed in Italy: An Inventory - Brita, Antonella; Hummel, Susanne; Helmholz, Karsten; Villa, Massimo (Aethiopica, 2017)
The report aims to introduce three little known collections of Gǝʿǝz manuscripts hosted in the following Italian institutions: Castello d’Albertis, fondo Sapeto (Genoa), Biblioteca Giovardiana, fondo Quattrociocchi, and Monumento Nazionale Abbazia di Casamari (both in Veroli, Frosinone). The forty-two manuscripts (codices and scrolls) preserved in the three collections were surveyed, digitized and analysed through non-invasive techniques in the course of two fieldworks conducted in May 2015 and June–July 2017. The present article, conceived as a preliminary report to a more detailed catalogue currently under preparation, describes how the manuscript collections emerged and provides an introductory description of the textual content and the physical features of each item.